Exploring terrorist targeting preferences - Libicki, Martin C.; Chalk, Peter; Sisson, Melanie (RAND, 2007)
Governments spend billions to protect against terrorism. Might it help to understand what al Qaeda would achieve with each specific attack? This book examines various hypotheses of terrorist targeting: is it (1) to coerce, (2) to damage economies, (3) to rally the faithful, or (4) a decision left to affiliates? This book analyzes past attacks, post hoc justifications, and expert opinion to weigh each hypothesis.
"MG-483."
Includes bibliographical references
Keywords: al-Qaida; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; Terrorismus; Terrorism -- United States -- Prevention; Ziel; Attentat; USA